Are environmental and sociodemographic factors associated with physical activity of pediatric oncologic patients and their parents? A cross-sectional study - Jean Augusto Coelho Guimarães; Sofia Wolker Manta; Ana Elisa Messetti Christofoletti; Vanessa Fabiana da Costa Sannomiya; Priscila Missaki Nakamura (Revista Brasileira de Atividade Física e Saúde, 2025)
Introduction: Physical activity (PA) during pediatric oncologic treatment provides health benefits to patients. However, different factors can facilitate or hinder this practice. Objective: Verify the association between  environmental and sociodemographic factors and leisure time and commuting-related physical activity (LTPA-CPA) of pediatric oncologic patients and their parents. Methods:Cross-sectional study in partnership between the University and the Reference Children’s Oncologic Center. Young patients (10-19 years old) diagnosed with cancer and at any stage of treatment participated, as well as their father or mother. Participants answered socioeconomic and sociodemographic questions, a questionnaire of PA for adolescents, and the environmental scale for youth, through telephone or face-to-face contact. Descriptive statistics, Student’s t-test, Pearson’s chi-square test, Poisson regression, Fisher’s exact test, and the Kappa index were used. A p-value of < 0.05 was considered statistically significant. Fisher’s exact test and Kappa Index (k) were performed to verify possible associations and concordance between adolescents and parents, with a p value <0.05. Results: 40 patients partic-ipated in this study (62.5% male), most diagnosed with leukemia (40%) and 40 parents (43.08 ± 7.67 years old; 73% female), 63% white ethnicity and 50% socioeconomic level C1/C2/ D-E. The mean LTPA-CPA by patients was 286.7 ± 238.6 min/week, and by parents it was 50.8 ± 99.7 min/week. There was no association between sociodemographic factors, PA of parents, and LTPA-CPA of patients (p > 0.05). There was a negative association between LTPA-CPA and recreational facilities (p = 0.04), and a positive association for greater neighborhood safety (p = 0.02). Conclusion: There was no association between sociodemographic factors and LTPA-CPA in pediatric patients and their parents. Greater neighborhood safety was associated with this practice.